Assessment of Metabolic Interaction between Repaglinide and Quercetin via Mixed Inhibition in the Liver: In Vitro and In Vivo - Ji-Min Kim; Seong-Wook Seo; Dong-Gyun Han; Hwayoung Yun; In-Soo Yoon (MDPI AG, 2021)
Repaglinide (RPG), a rapid-acting meglitinide analog, is an oral hypoglycemic agent for patients with type 2 diabetes mellitus. Quercetin (QCT) is a well-known antioxidant and antidiabetic flavonoid that has been used as an important ingredient in many functional foods and complementary medicines. This study aimed to comprehensively investigate the effects of QCT on the metabolism of RPG and its underlying mechanisms. The mean (range) IC50 of QCT on the microsomal metabolism of RPG was estimated to be 16.7 (13.0-18.6) μM in the rat liver microsome (RLM) and 3.0 (1.53-5.44) μM in the human liver microsome (HLM). The type of inhibition exhibited by QCT on RPG metabolism was determined to be a mixed inhibition with a Ki of 72.0 μM in RLM and 24.2 μM in HLM as obtained through relevant graphical and enzyme inhibition model-based analyses. Furthermore, the area under the plasma concentration versus time curve (AUC) and peak plasma concentration (Cmax) of RPG administered intravenously and orally in rats were significantly increased by 1.83- and 1.88-fold, respectively, after concurrent administration with QCT. As the protein binding and blood distribution of RPG were observed to be unaltered by QCT, it is plausible that the hepatic first-pass and systemic metabolism of RPG could have been inhibited by QCT, resulting in the increased systemic exposure (AUC and Cmax) of RPG. These results suggest that there is a possibility that clinically significant pharmacokinetic interactions between QCT and RPG could occur, depending on the extent and duration of QCT intake from foods and dietary supplements.